2018
DOI: 10.3389/fnbeh.2018.00158
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Memory Impairment Differs by Sex in a Rodent Model of Pediatric Radiotherapy

Abstract: Although an effective treatment for pediatric brain tumors, cranial radiation therapy (CRT) damages surrounding healthy tissue, thereby disrupting brain development. Animal models of pediatric CRT have primarily relied on visual tasks to assess cognitive impairment. Moreover, there has been a lack of sex comparisons as most research on the cognitive effects of pediatric CRT does not include females. Therefore, we utilized olfaction, an ethologically relevant sensory modality, to assess cognitive impairment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Cell proliferation in the SVZ in rodents has been linked to performance on olfactory-based learning and memory tests [26,27,28] and is negatively affected by radiation exposure [28,29]. The Radiation Dose X Time Following Radiation Exposure ANOVA revealed a significant main-effect of Time Following Radiation Exposure (F(1,17) = 5.9, p = 0.032, effect size: ω 2 = 0.207).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation in the SVZ in rodents has been linked to performance on olfactory-based learning and memory tests [26,27,28] and is negatively affected by radiation exposure [28,29]. The Radiation Dose X Time Following Radiation Exposure ANOVA revealed a significant main-effect of Time Following Radiation Exposure (F(1,17) = 5.9, p = 0.032, effect size: ω 2 = 0.207).…”
Section: Resultsmentioning
confidence: 99%
“…Further, this pattern of dose- and time-dependent social recognition deficits appears to be different in female subjects, indicating a possible sex difference following radiation exposure that needs to be further examined [8,26,38,39]. For example, female mice do not develop radiation-induced social recognition deficits following the multi-ion GCR-like exposure described above [30].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, children who received whole-brain RT (WBRT) with chemotherapy had smaller amygdala volumes than those treated with chemotherapy alone, but amygdala volumes were similar in controls (patients with ALL who had not yet started treatment) and children who received chemotherapy. Pre-clinical data also implicate radiotherapy to the amygdala in changes to olfactory memory processing: a study using a mouse model of pediatric radiotherapy revealed significant reductions in diffusion tensor imaging of amygdala volume three months post-WBRT 42 . Cognitively, irradiated male mice had impaired odor-recognition memory in adulthood, compared to nonirradiated males.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few cancer modelling studies have assessed the role of estrogen in these neurobehavioral results through ovariectomy, hormone replacement, or estrogen modulator treatments. One relevant study demonstrates that long-term olfactory recognition memory impairments in mice receiving cranial radiation therapy are dependent upon estrous stage (Perez et al, 2018). Cancer anorexia is also hypothesized to be influenced by sex-related hormones (Varma et al, 2001).…”
Section: Female Cancer Effects On Brainmentioning
confidence: 99%